Low Interest in Using the Wemale Language Among the Youth of Kamarian Village, West Seram Regency - Dokolamo, Hamid; Kainama, Frengky (Universitas Pattimura, 2022)
This study aims to determine the interest in using the Wemale language among the younger generation. The research method used in this research is qualitative research and was conducted from July 11 to August 11, 2022, in Kamarian Country, Kairatu District, West Seram Regency, Maluku. This study's data sources were obtained from informants/resources, observation, documentation, and literature. The study results show that the Wemale language has existed and been used by the people since they still lived in Nunusaku and has become a distinctive language since their ancestors during the war. The Wemale language is currently only used by the community in certain traditional ceremonies, such as bringing wealth, asking for a wife, and inaugurating a king. It is also used for secret talks. The factors for the loss of the language of the land in the Kamarian Country were the influx of foreign culture, the existence of a ban by the Dutch Colonial Government, the family environment, education, and the development of Science and Technology.